2015
DOI: 10.1002/mgg3.157
|View full text |Cite
|
Sign up to set email alerts
|

Multigene panel analysis identified germline mutations of DNA repair genes in breast and ovarian cancer

Abstract: Approximately 5–10% of all breast and/or ovarian cancer cases are considered as inherited. BRCA1 and BRCA2 tumor suppressor genes account for a high penetrance of hereditary cases, but familial cases without mutations in these genes can also occur. Despite their low penetrance, other hereditary cancer-related genes are known to be associated with breast and ovarian cancer risk. However, the extent to which these genes prevail in breast and ovarian cancer remains to be elucidated. To estimate the frequency of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 32 publications
(28 reference statements)
3
58
0
3
Order By: Relevance
“…In our study, no deleterious truncating variant was identified, and the allele counts of the observed missense variants were not statistically different from that in HGVD (Tables and ). Similar results are reported by Hirotsu and Nakagomi et al . They also detected no obvious deleterious truncating variants in Japanese familial breast cancer cases.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, no deleterious truncating variant was identified, and the allele counts of the observed missense variants were not statistically different from that in HGVD (Tables and ). Similar results are reported by Hirotsu and Nakagomi et al . They also detected no obvious deleterious truncating variants in Japanese familial breast cancer cases.…”
Section: Discussionsupporting
confidence: 90%
“…Germline mutations for BRCA1/2 and PALB2 were analyzed using targeted sequencing, as previously reported (4,19,22). Briefly, the Ion AmpliSeq™ BRCA1 and BRCA2 and the Ion AmpliSeq™ BRCA Reflex Hereditary Cancer Research panels (Thermo Fisher Scientific, Inc., Waltham, MA, USA) were used, targeting the whole exons of the BRCA1/2 genes and an additional 25 hereditary cancer-associated genes (22,23).…”
Section: Case Reportmentioning
confidence: 99%
“…Briefly, the Ion AmpliSeq™ BRCA1 and BRCA2 and the Ion AmpliSeq™ BRCA Reflex Hereditary Cancer Research panels (Thermo Fisher Scientific, Inc., Waltham, MA, USA) were used, targeting the whole exons of the BRCA1/2 genes and an additional 25 hereditary cancer-associated genes (22,23). Buffy coat DNA was used as a template, and the sequencing library was generated using an AmpliSeq Library kit 2.0 (Thermo Fisher Scientific, Inc.) (24-31).…”
Section: Case Reportmentioning
confidence: 99%
“…The current medicine strategy against ovarian cancer emphasizes targeting the dominant factor(s) during the clinical trials. One of the efficient approaches is developed by trying to identify the germline and sporadic key mutations in the primary site of the tumors [6769]. The study here not only reveals the DNA damage as a potential driver of ovarian tumorigenesis, but also provides possible gene targets for clinical treatment.…”
Section: Resultsmentioning
confidence: 99%